2007
DOI: 10.1139/z07-090
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in activity of bat species differing in hunting tactics: effects of weather, moonlight, food abundance, and structural clutter

Abstract: Different foraging tactics in related animal taxa may be expected to cause species-specific differences in sensitivity to temporal and spatial variations of resources. To test this, we studied spatiotemporal dynamics of flight and foraging activity in seven insectivorous bat species in northern Poland using broadband ultrasound detection, recording of weather conditions, insect abundance, moon phase, and cover of floating vegetation. The seven species studied comprised six (genera Eptesicus Rafinesque, 1820, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 76 publications
2
90
0
Order By: Relevance
“…Although this was proven in many species of aerial hawking bats (e.g., Racey & Swift 1985;Rydell 1989;Catto et al 1995;O'Donnell 2000;Ciechanowski et al 2007), Daubenton's bats seem to be quite tolerant to relatively very low temperatures (Dietz & Kalko 2007) and they were observed foraging at as low temperatures as -3 • C (Ciechanowski et al 2007). Accordingly with observations above, we did not observe any significant effect of minimum nightly temperature on the activity of radio-tracked Daubenton's bats.…”
Section: Foraging Timesupporting
confidence: 68%
“…Although this was proven in many species of aerial hawking bats (e.g., Racey & Swift 1985;Rydell 1989;Catto et al 1995;O'Donnell 2000;Ciechanowski et al 2007), Daubenton's bats seem to be quite tolerant to relatively very low temperatures (Dietz & Kalko 2007) and they were observed foraging at as low temperatures as -3 • C (Ciechanowski et al 2007). Accordingly with observations above, we did not observe any significant effect of minimum nightly temperature on the activity of radio-tracked Daubenton's bats.…”
Section: Foraging Timesupporting
confidence: 68%
“…the bats appear to be responding to the effect of light on their prey behaviour [76]. Another water surface forager whose activity is negatively correlated with moonlight is Daubenton's bat (Myotis daubentonii) [77]. A study of activity levels of the white-throated round-eared bat (Lophostoma silvicolum), a gleaning insectivorous bat which relies mainly on passive acoustic cues to find prey, and its main prey item katydids, found that both were significantly more active during the dark periods associated with new Moon [78], suggesting that the reduced activity can be attributed to reduced prey availability [78].…”
Section: (D) Mammalsmentioning
confidence: 99%
“…This problem, however, affects this study only to a minor extent. Intensive summer mist netting conducted in the Gdańsk Pomerania region revealed that more than 90 % of Myotis bats captured belong to Daubenton's bat Myotis daubentonii (Ciechanowski 2002;Ciechanowski et al 2002;Ciechanowski et al 2007) and this allowed the assumption that most Myotis echolocation calls recorded there during the summer season are emitted by the same species. If possible, the presence of M. daubentonii was confirmed by either visual observation (i.e.…”
Section: Analysis Of Bat Callsmentioning
confidence: 99%